Changes in attack behavior and activity in EphA5 knockout mice - Mamiya, Ping Chao (2008)
During development, Eph tyrosine kinase receptors and their ephrin ligands function as axon guidance molecules while, in adults, these molecules appear to be involved in the regulation of neural plasticity and emotion. The absence of EphA5 receptor mediated forward signaling may cause alterations in connectivity of neural networks and boundary formation during development, including central monoaminergic systems. In the present studies, we demonstrated altered aggressive responses by animals lacking functional EphA5 receptors. These behavioral changes were accompanied by altered concentrations of serotonin (5-HT) and the metabolite, 5-HIAA, in the hypothalamus. The changes of serotonin activity in hypothalamus also result in increase of body weight in EphA5 knockout mice. Furthermore, EphA5 knockout mice exhibited a significant decrease in activity levels following exposure to naïve intruders in their home cages. We conclude that the EphA5 receptor may be involved in mediation of aggressive behavior regulated, in part, by hypothalamic serotonin.